Role of pilot testing in the use of learning tool for year 6 elementary school student / Siti Hajar Md.Jani and Dr. Jamali Wagiman - Md.Jani, Siti Hajar; Wagiman, Jamali (Academy of Language Studies, Universiti Teknologi MARA Negeri Sembilan Branch, Rembau Campus, 2023)
Science, Technology and Innovation become integral part of school curriculum in primary as well as secondary education. Sekolah Kebagsaan Kuala Pilah has invited us to conduct and facilitate a program for this purpose. Under year 6 syllabus, reproductive and nervous system is included as part of Science Subject. We propose to focus on Human Reproductive System as main theme of the program by exposing student with several Learning Tool to help them to understand the subject well. At the end of two months of preparation, we conducted a Pilot Test to ensure that the methods, material and timing are well comprehend by the student, 12 students among UiTM staff children is involved in this Pilot Study. The outcome of this Pilot Study is crucial in the sense that we are able to identify issues related to the program. The actual program was taken place in SK Kuala Pilah on 8th September 2023 with full cooperation given by the school officials. The Survey that taken place after the program were also granted by Kuala Pilah’s Education Office.